The Impact of Patient and Provider Factors on Depression Screening of American Indian and Alaska Native People in Primary Care - Denise A. Dillard; Clemma J. Muller; Julia J. Smith; Vanessa Y. Hiratsuka; Spero M. Manson (SAGE Publishing, 2012)
Introduction : The US Preventive Services Task Force recommends routine depression screening in primary care, yet regular screening does not occur in most health systems serving Alaska Native and American Indian people. The authors examined factors associated with administration of depression screening among Alaska Native and American Indian people in a large urban clinic. Methods : Medical records of 18 625 Alaska Native and American Indian adults were examined 1 year after implementation of a depression screening initiative. Multilevel logistic regression models examined associations between patient and provider factors and administration of the Patient Health Questionnaire-9. Results : Forty-seven percent of patients were screened. Women were more likely than men to be screened (50% vs 43%, P < .001). Increased screening odds were associated with older age, increased service use, and chronic disease ( P < .001) but not with substance abuse disorders or prior antidepressant dispensation. Women previously diagnosed with depression had higher odds of screening ( P = .002). Men seen by male providers had higher odds of screening than did men seen by female providers ( P = .040). Screening rates peaked among providers with 2 to 5 years of employment with the clinic. Limitations : Cross-sectional analysis of medical record data was of unknown reliability; there were limited sociodemographic data. Conclusions : Even with significant organizational support for annual depression screening, primary care providers systematically missed men and patients with infrequent primary care visits. Outreach to male patients and additional supports for primary care providers, especially in the first years of practice, may improve screening and treatment for depression among Alaska Native and American Indian people.